2010
DOI: 10.1007/978-3-642-14616-9_28
|View full text |Cite
|
Sign up to set email alerts
|

Fire Data Analysis and Feature Reduction Using Computational Intelligence Methods

Abstract: Fire is basically the fast oxidation of a substance that produces gases and chemical productions. These chemical productions can be read by sensors to yield an insight about type and place of the fire. However, as fires may occur in indoor or outdoor areas, the type of gases and therefore sensor readings become different. Recently, wireless sensor networks (WSNs) have been used for environmental monitoring and real-time event detection because of their low implementation costs and their capability of distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…First, sensor nodes are vulnerable to failure because the WSNs are often deployed in harsh environments [18][19][20][21]. Outliers are commonly found in datasets collected by the WSNs installed in harsh environments [22,23].…”
Section: Outlier Detection In Wsn Applicationsmentioning
confidence: 99%
“…First, sensor nodes are vulnerable to failure because the WSNs are often deployed in harsh environments [18][19][20][21]. Outliers are commonly found in datasets collected by the WSNs installed in harsh environments [22,23].…”
Section: Outlier Detection In Wsn Applicationsmentioning
confidence: 99%
“…Our approach is based on implementing classification techniques on wireless sensor nodes attached to patients' body, online evaluation of the classification results on individual nodes, and fusing results of various nodes to resolve possible conflicts between sensor nodes and reach a consensus. Previously in Bahrepour, Zhang et al 2009;Bahrepour, van der Zwaag et al 2010), we have shown capability of machine learning based classification techniques in distributed detection of environmental events such as fire. There is no reason to believe that classification techniques used in other domains are not applicable for medical domain.…”
Section: Introductionmentioning
confidence: 99%
“…Fire #1 dataset is real dataset containing three types of fires, i.e., flaming fires (fires that produce massive heat), smoldering fires (fires that produce massive smoke) and nuisances (fire-like incidents such as smoking a cigarette or toasting a bread) [108]. The dataset is obtained from the National Institute of Standard and Technology (NIST) website [109] by merging two smoldering fire datasets (SDC31, SDC40), two flaming fire datasets (SDC10, SDC14) and two nuisance resource datasets (MHN06, MHN16).…”
Section: Fire #1 Datasetmentioning
confidence: 99%
“…Later on in this chapter, we also discuss † † This chapter is partially published with the title: "Fire data analysis and feature reduction using computational intelligence methods". In: Advances in Intelligent Decision Technologies -Proceedings of the Second KES International Symposium IDT 2010, 28-30 July 2010, Baltimore, Maryland, USA [108].…”
Section: Introductionmentioning
confidence: 99%